K.H. A. MUSTOFA BISRI: PENYAIR YANG MENYIKAPI KEOTORITERAN MASA ORDE BARU DAN KEBEBASAN MASA REFORMASI - Mujiningsih, Erlis Nur (ATAVISME, 2007)
This article is purposed to describe the composition of Mustofa Bisri. By credo la ilaha ilallah, Mustafa Bisri creates the painting and literature area without pay attention to the comment of the critics about his work. His works are considered as a part of amar makrufnahi munkar that he wants to be built, with credo and that spirit, Mustofa Bisri presents more issues related with the correlation between man and his peer, in social level and a man with his god in individual level. His critics are not only for an administrator that related with the people but also to the community and an individual. Even though his critics to the administration are too sharp, Mustofa Bisri is always escaped from the capture and restraint. It is not only because of his figure as Kiai Nadiatul Ulama that supported by his students but also because of his competence in forming his critics to the language that is impressed jokes, by turning around the words like his poem mbeling. His poems reflex his view and attitude to the authorization in the New Orde era and the freedom in the reformation era.